Anterior Knee Pain and Sensitivity Deficits after Anterior Cruciate Ligament Reconstruction: BTB vs 4 ST/G vs All-Inside - Orlando Jose de Almeida Branco Simões (2021)
Purpose To study pain and sensory alterations of 75 (three cohorts of 25 patients) athletic patients that underwent different anatomic arthroscopic ACLr surgery techniques. The cohorts were divided in the bone-patellar tendon-bone autograft cohort, the quadruple strand semitendinosus and gracilis autograft cohort and the quadruple strand semitendinosus autograft all-inside cohort. Methods We conducted a retrospective cohort study of pain and sensory alterations. All these patients followed a similar rehabilitation protocol, being 2 years the minimal follow-up time. Pain was characterized by duration and anatomical location and sensory deficits were evaluated concerning duration and affected area. Patients also scored on 3 different subjective tests: KWT; LKSS and IKDC-SKF and were divided according to its TALS. Results The mean AKP duration amongst the 3 cohorts was 1.8 ± 4.5 months and was significantly smaller in the 4ST/G cohort. The majority of patients of the BTB cohort located pain on the patellar tendon while patients in the 4ST/G and All-Inside cohorts referred that it was diffuse. At 15 days' post-surgery, hypoesthesia was reported by 42 patients and was significantly higher on the BTB cohort and less in the All-Inside cohort. At 2-year followup, the All-Inside cohort had no patients with hypoesthesia. In the BTB cohort, the sensitive alterations were only located on the area innervated by the IPBSN. The 4ST/G cohort located the hypoesthesia in the area innervated by the IPBSN and in the area of the LSCN. The All-Inside group located the sensitive alterations mostly in the LSCN. The KWT was painful in BTB and 4ST/G patients and reported 0% for the All-Inside cohort. No statistic relevance was found for the IKDC-SKF and LKSS tests. Conclusions All cohorts referred pain and sensitive alterations. The arthroscopic ACLr using BTB autograft seems to condition a higher number of anterior knee pain and hypoesthesia on medium post-operative outcomes and KWT was more often reported. The 4ST/G group had the smallest duration of AKP. The All-Inside cohort showed, globally, a lower number of complaints and a shorter time of symptom persistence, namely in terms of sensory deficit in the postoperative period.